2021
DOI: 10.3390/fluids6020080
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on an Interface Compression Method for the Volume of Fluid Approach

Abstract: Many thermohydraulic issues about the safety of light water reactors are related to complicated two-phase flow phenomena. In these phenomena, computational fluid dynamics (CFD) analysis using the volume of fluid (VOF) method causes numerical diffusion generated by the first-order upwind scheme used in the convection term of the volume fraction equation. Thus, in this study, we focused on an interface compression (IC) method for such a VOF approach; this technique prevents numerical diffusion issues and maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…is the unit vector normal to the interface, and c α is a compression coefficient that determines the strength of the compression, e.g. c α = 0 for no compression, c α = 1 for conservative compression and c α > 1 for high compression (Larsen, Fuhrman & Roenby 2019;Okagaki et al 2021).…”
Section: Equations and Numerical Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…is the unit vector normal to the interface, and c α is a compression coefficient that determines the strength of the compression, e.g. c α = 0 for no compression, c α = 1 for conservative compression and c α > 1 for high compression (Larsen, Fuhrman & Roenby 2019;Okagaki et al 2021).…”
Section: Equations and Numerical Methodsmentioning
confidence: 99%
“…2019; Okagaki et al. 2021). In the present case, we found that the intermediate numerical diffusion associated with the use of relatively fine spatial and temporal resolution levels, together with the adoption of mixed first- and second-order-accurate schemes in time and space, can be balanced reasonably by using an intermediate value of the compression coefficient .…”
Section: Direct Numerical Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, a discretisation scheme is devised for the advection terms, with the compressive interface capturing (CICSAM) and piecewise linear interface construction (PLIC) being the most widespread (we refer to [40] for a detailed explanation and derivation).…”
Section: Reduction Of a Multiphase Model With Manifold Transformationmentioning
confidence: 99%